Competitive manufacturing of 3D thermoplastic composite panels based on multi-layered woven structures for lightweight engineering. (1st December 2015) - Mountasir, A.; Hoffmann, G.; Cherif, Ch.; Löser, M.; Großmann, K.
Abstract: Multi-layered woven structures are characterised by non-crimp fibre arrangement of the high-performance warp and weft yarns such as CF and GF, allowing optimal use of the fibre substance strength and subsequently increased the mechanical properties of their composites. This article illustrates the development and the successfully implementation of large three-dimensional (3D) thermoplastic composites as woven spacer fabrics and as woven panels with integrated stiffeners in the transversal and longitudinal direction continuously manufactured from the 3D multi-layered woven fabrics in single process step. Furthermore, it will be proved that the investigation of the mechanical properties of the composites made of the 3D multi-layered woven fabrics compared to woven fabrics with yarn-crimp provides high mechanical values, which can be significantly adjusted for the required composite components. The 3D thermoplastic composite panels as Fibre-reinforced Plastics (FRP) are excellently suited for different applications in lightweight engineering such as aircraft, automotive industry and machine engineering.